Influence of MTP on Surface Roughness and Geometric Accuracy of Machined Surface at WEDM - Straka, Luboslav; Dittrich, Gabriel (International Journal of Engineering and Management Sciences, 2020)
Electrical discharge machining technology is one of the most precise machining methods. Therefore, even the smallest deviation of micro and macro geometry generally has a significant impact on the overall quality of products produced by this progressive technology. The quality of the machined surface after Wire Electrical Discharge Machining (WEDM) is influenced by a large number of factors, most of which are influenced by the Main Technological Parameters (MTP). The aim of the paper was to describe the results of experimental research aimed at assessing the impact of MTP for WEDM on the quality of machined surface in terms of geometric accuracy and roughness parameters Ra and Rz. The samples were made of high alloyed ledeburitic chromium-molybdenum-vanadium steel designated EN X155CrVMo12-1 on a Sodick AQ535 electroerosion machine. The tool used was a standard compact brass wire  0.25 mm with the designation Elecut Brass CuZn37.